Low Impact of Avian Pox on Captive-Bred Houbara Bustard Breeding Performance - Le Loc’h, Guillaume; Souley, Mam-Noury Amadou; Bertagnoli, Stéphane; Paul, Mathilde C. (Frontiers in Veterinary Science, 2017)
Avian pox, a disease caused by avipoxviruses, is a major cause of decline of some endangered bird species. While its impact has been assessed in several species in the wild, effects of the disease in conservation breeding have never been studied. Houbara Bustard species (Chlamydotis undulata and Chlamydotis macqueenii), whose populations declined in the last decades, have been captive-bred for conservation purposes for more than 20 years. While mortality and morbidity induced by avipoxviruses can be controlled by appropriate management, the disease might still affect bird breeding performance and jeopardize the production objectives of conservation programs. Impacts of the disease was studied during two outbreaks in captive-bred juvenile Houbara bustards in Morocco in 2009-2010 and 2010-2011, by modelling the effect of the disease on individual breeding performance (male display and female egg production) of 2797 birds during their first breeding season. Results showed that the impact of avian pox on the ability of birds to reproduce and on the count of displays or eggs is low, and mainly non-significant. The absence of strong impact compared to what could be observed in other species in the wild may be explained by the controlled conditions provided by captivity, especially the close veterinary monitoring of each bird. Those results emphasise the importance of individual management to prevent major disease emergence and their effects in captive-breeding of endangered species.